Improve Student Learning Outcomes in Multiplication Learning Mixed Fractions Using Teams Games Tournament (TGT) Model - Mardiyani, Anisa; Suryana, Yusuf; Febriani, Winarti Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
The problem in this study was the low student learning outcomes in mathematics learning the subject of multiplication of mixed fractions in class V. The purpose of this study was to see an increase in student learning outcomes in learning mixed fraction multiplication using the TGT learning model in class V SDN 2 Cigembor, Ciamis District, Regency. Ciamis. The population in the study were 30 grade students of SDN 2 Cigembor. The method used in this research is Classroom Action Research Methods (PTK) according to Kemmis and Mc. Taggart which consists of four stages: planning, implementing, observing, reflecting. This research was conducted in two cycles. The instruments used in this study were evaluation instruments, teacher performance instruments, and student activity instruments. Based on the results of the evaluation test data from cycle I to cycle II, it shows that in the first cycle the average student learning outcomes were 74.40 and learning completeness was 57%, while in the second cycle the average student learning outcomes were 79.83 and completeness learn by 87%. Based on the results of the research, it can be concluded that the use of the TGT learning model can improve student learning outcomes in the multiplication of mixed fractions in class V SDN 2 Cigembor, Ciamis District, Ciamis Regency, Academic Year 2019/2020.